Tough talking cowboy - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Wild Rose Ranch series., 2020)
"Ex-Army Ranger Drake McGrath has come home to Montana, locked in a battle with himself, lashing out at those who love him most - driving away his ex-fiancée and alienating his family. But Adria Holloway sees beyond Drake's tough talk to the raw pain beneath. To help them both, Adria makes Drake a shocking deal - a no-strings relationship that'll help them both face down their demons. Maybe it's a way for her and Drake to heal each other, one sizzling night at a time."--Publisher.